2017
DOI: 10.21067/jem.v13i3.2024
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Menentukan Kepuasan Kerja Pegawai

Abstract: The purpose of this study is to determine the factors that affect job satisfaction of employees in regionally owned enterprise. Based on the background to the problem, earlier theories and researches, these factors are work environment, organizational culture and work motivation . The study was conducted at the Prodexim Regional Company of South Sulawesi. Used of 70 people as respondents. The analysis technique used is path analysis. The result of the research shows that the work environment and organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
1
3
0
9
Order By: Relevance
“…The results achieved in this study also strengthen and emphasize the results of research conducted previously by Kurniawan & Hendri [21], that it is true that some factors that can influence job satisfaction are the right motivation and reward system. Masilawati & Hope [22] states there is a positive and significant impact of motivation and appreciation on job satisfaction.…”
Section: Effect Of Work Motivation and Reward System On Teacher Job Satisfactionsupporting
confidence: 87%
“…The results achieved in this study also strengthen and emphasize the results of research conducted previously by Kurniawan & Hendri [21], that it is true that some factors that can influence job satisfaction are the right motivation and reward system. Masilawati & Hope [22] states there is a positive and significant impact of motivation and appreciation on job satisfaction.…”
Section: Effect Of Work Motivation and Reward System On Teacher Job Satisfactionsupporting
confidence: 87%
“…Hal berbeda dengan penelitian yang dilakukan oleh (Gunawan & Kusniawati, 2019), (Arifin, Pasinringi, & Palu, 2018), (Herman, 2016), (Limanjaya, 2018), (Pitasari, Imas Ayu Aulia, Perdhana, 2018), (Astuti et al, 2020) dan (Kouni, Koutsoukos, & Panta, 2018) yang menggunakan metode penelitian kualitatif dalam mengungkap kepuasan kerja. Hasil penelitian-penelitian tersebut menyatakan bahwa kepuasan kerja dipengaruhi oleh beberapa faktor diantaranya yaitu promosi, lingkungan kerja, pekerjaan itu sendiri, rekan kerja, dan pengawasan atasan.…”
Section: Pendahuluanunclassified
“…Pekerja bekerja bergantung pada perbedaan antara apa yang didapat dengan apa yang diinginkan oleh pekerja, apabila yang didapat pekerja secara nyata lebih besar daripada apa yang diinginkan maka hal ini akan menimbulkan kepuasan kerja. Pendapat ini pun sesuai dengan penelitian yang dilakukan oleh (Rachmady, 2019) (Gunawan & Kusniawati, 2019), (Limanjaya, 2018), (Pitasari, Imas Ayu Aulia, Perdhana, 2018) dan (Tentama et al, 2019) yang menyatakan bahwa semakin tinggi beban kerja atau ketidaksesuaian pekerjaan maka semakin memunculkan ketidakpuasan dan sebaliknya semakin rendah beban kerja dan ketidaksesuaian pekerjaan semakin memeunculkan kepuasan dalam bekerja. Seluruh Informan menyatakan bahwa beban kerja Account Representative Pelayanan tidak terlalu berat dan jenis pekerjaannya sudah ditentukan dengan pasti sehingga hal inilah yang menimbulkan kepuasan kerja yang tinggi pada Account Representative Pelayanan.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Research on job satisfaction of Puskesmas staff conducted by Agung Gunawan et al at the Cipaku Health Center, Ciamis Regency (2019) found that 56% satisfied staff were caused by welfare factors, relationships between colleagues, quality of supervision, job characteristics, and opportunities for development/promotion (Gunawan and Kusniawati, 2019). Determinants of job satisfaction in 3 Puskesmas of Merangin Regency representing mountainous, transmigration, and urban areas carried out by Novia Susianti (2019) are financial incentives, relationshipswith colleagues, and motivation.…”
Section: Introductionmentioning
confidence: 99%